IMPLEMENTASI KEBIJAKAN BANTUAN SOSIAL BENCANA BANJIR DI KECAMATAN DAYEUHKOLOT KABUPATEN BANDUNG - Sugih Candra Kayat (Jurnal Dialektika Politik, 2023)
The expansion of an establishment makes a new problem in the surrounding environment so that claims to a safe state, from regional disasters, especially flood disasters in the Dayeuhkolot District, Bandung Regency, become a common interest, especially residents affected by flood disasters in the sub-district, significant population development makes a new challenge for all parties affected. However, the dedication of all sectors involved in the implementation of the distribution of social assistance for flood victims is in accordance with common expectations. As well as in the important sector of assistance from the informal sector in the implementation of the distribution of community contributions channeled does not run effectively. Based on these problems, the study is intended to describe how the implementation of policies, obstacles and efforts made in the process of implementing policies in the distribution of social assistance to victims affected by the disaster. The form of study in this research uses a strategy that emphasizes the quality of the entity. Data collection is done through consultation, observation, and processing. The data description used is an explication model, where the data collected is then described in the form of an interpretative description above. Based on the research, the obstacles faced by the local government of Bandung Regency in implementing the policoes for the distribution of social assistances for flood victims include a lack of awareness of the duties and function of a related organizations, people who tend not to understand the existence of regional regulations which contain policies regardimg the implementation of aid distribution, social victims of the flood disaster in Dayeuhkolot sub-district.